Designing Robust, Breathable, and Antibacterial Multifunctional Porous Membranes by a Nanofluids Templated Strategy. (9th September 2020) - Ju, Junping; Hao, Longyun; Yang, Shiwen; Wang, Dandan; Zhang, Yongzhi; Yuan, Hua; Yin, Xianze; Tan, Yeqiang
Abstract: Advanced medical dressings need to meet these requirements of breathability, moisture absorption balance, antibacterial activity, and mechanical strength. Both breathability and moisture absorption balance strongly depend on the porous structure that inversely sacrifice their mechanical properties and bulk antibacterial activity. Herein, multifunctional porous structure is designed that can synchronously realize excellent antibacterial activity, breathability, superhydrophilicity, and enhanced mechanical properties just using nanofluids templating. The pore sizes, density, and functionality of porous polymers are regulated through nanofluids loading and multiple functional components including inorganic nanoparticles core and organic corona/canopy composed of organic long chains with different charges. An ionically tethered, nonylphenol polyoxyethylene ether sulfate as a canopy of nanofluids can be removed with sodium chloride solution to form porous structure, greatly improving the breathability of membrane and achieving superhydrophilicity to obtain moisture absorption balance. Meantime, exposed polysiloxane quaternary ammonium salts as covalently bonded corona of nanofluids exhibit excellent antibacterial activity. Finally, nanoparticles core endows supreme tensile strength ratio (115%) of porous membrane. Overall, nanofluids templating approach is expected to develop into a universal strategy to construct a series of multifunctional porous polymer materials via varying the component of nanofluids, which provide a promising application in biomedicine, human health, and life science. Abstract : A universal strategy using nanofluids as a multifunctional porogen is developed to fabricate a porous structure, enhance mechanical properties, and introduce multiple functions of breathability, antibacterial activity, and superhydrophilicity simultaneously. Furthermore, the whole pore‐forming condition is a convenient and environment‐friendly approach without the consumption of excessive energy and organic solvents, which can promote the development of novel porous polymer membranes with functional micropores.